2020
DOI: 10.1002/dc.24650
|View full text |Cite
|
Sign up to set email alerts
|

The ATA classification and TI‐RADS ACR predict not only benignity but also the histology of nonbenign tumors in thyroid nodules with indeterminate cytology

Abstract: Ultrasonographic features are useful to estimate the risk of malignancy in thyroid nodules with indeterminate cytology. Two issues regarding the role of ultrasonography (US) in these nodules are currently emerging. First, instead of individual features, the current recommendation is to use classifications that consider a set of ultrasonographic findings. 1,2 At present, the two most widely used classifications are that of the American Thyroid Association (ATA) 1 and the Thyroid Imaging Reporting and Data Syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 6 publications
0
10
0
Order By: Relevance
“…9,32 A thyroid nodule with high suspicion sonographic pattern is not only more frequently found to be cancer than a nodule with low suspicion sonographic pattern, but it is also more frequently found to be a papillary thyroid cancer. 9,32 Conversely, a follicular-pattern lesion is more likely found in nodules with low suspicion sonographic patterns. 9,32 This is the consequence of having derived high suspicion features from the analyses of a series in which most malignancies were papillary thyroid cancers.…”
Section: Institutional Rate Of Malignancy Of Each Category Of Sonogra...mentioning
confidence: 99%
See 3 more Smart Citations
“…9,32 A thyroid nodule with high suspicion sonographic pattern is not only more frequently found to be cancer than a nodule with low suspicion sonographic pattern, but it is also more frequently found to be a papillary thyroid cancer. 9,32 Conversely, a follicular-pattern lesion is more likely found in nodules with low suspicion sonographic patterns. 9,32 This is the consequence of having derived high suspicion features from the analyses of a series in which most malignancies were papillary thyroid cancers.…”
Section: Institutional Rate Of Malignancy Of Each Category Of Sonogra...mentioning
confidence: 99%
“…9,32 Conversely, a follicular-pattern lesion is more likely found in nodules with low suspicion sonographic patterns. 9,32 This is the consequence of having derived high suspicion features from the analyses of a series in which most malignancies were papillary thyroid cancers. Thus, the genetic alterations found in cytologically indeterminate thyroid nodules are also expected to be different according to their sonographic features.…”
Section: Institutional Rate Of Malignancy Of Each Category Of Sonogra...mentioning
confidence: 99%
See 2 more Smart Citations
“…Only two Brazilian studies on this subject were found 15 , 16 . Neither of them finds relevant differences between ATA and ACR-TIRADS.…”
Section: Introductionmentioning
confidence: 99%